2016
DOI: 10.1111/nph.14357
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen transport in the orchid mycorrhizal symbiosis – further evidence for a mutualistic association

Abstract: This article is a Commentary on Fochi et al., 213: 365–379.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 18 publications
(42 reference statements)
3
50
0
3
Order By: Relevance
“…In addition, TcGS1 and TcGOGAT, the fungal genes encoding glutamine synthetase and glutamate synthase in the N assimilation pathway, are also up-regulated in mycorrhizal protocorms. A commentary of this study by Dearnaley and Cameron (2017) concluded that the fungus, T. calospora, may receive ammonium from its orchid host, S. vomeracea, during seed germination and protocorm development. Therefore, a true mutualism may be also present in the initially mycoheterotrophic stage of autotrophic orchids or myco-heterotrophic orchids [29].…”
Section: Nutrient Exchange Between Orchids and Mycorrhizal Fungimentioning
confidence: 93%
See 4 more Smart Citations
“…In addition, TcGS1 and TcGOGAT, the fungal genes encoding glutamine synthetase and glutamate synthase in the N assimilation pathway, are also up-regulated in mycorrhizal protocorms. A commentary of this study by Dearnaley and Cameron (2017) concluded that the fungus, T. calospora, may receive ammonium from its orchid host, S. vomeracea, during seed germination and protocorm development. Therefore, a true mutualism may be also present in the initially mycoheterotrophic stage of autotrophic orchids or myco-heterotrophic orchids [29].…”
Section: Nutrient Exchange Between Orchids and Mycorrhizal Fungimentioning
confidence: 93%
“…However, recent evidence suggests that not only carbohydrates but also lipids can be transferred from host plants to fungi as C resources [27,28]. The mechanisms of how ectomycorrhizal and arbuscular mycorrhizal fungi take up and transfer mineral nutrients to their host plants for exchanging C resources are extensively studied; however, much less attention has been paid to ericoid and orchid mycorrhizal fungi [3,23,29]. Several detailed reviews on the mutualistic interactions between plants and fungi that form ectomycorrhizal or arbuscular mycorrhizal symbiosis have been published [3,[23][24][25][26]30].…”
Section: Nutrient Exchange Between Orchids and Mycorrhizal Fungimentioning
confidence: 99%
See 3 more Smart Citations